Study Of Triglycerides in Vegetable Oils by Gas Chromatography - Ergashev I.M; Mamirzayev M. A; Sedalova I.S; Suyunov Sh (Genius Journals, 2022)
As a result of this work, oils extracted from some melons were converted to methyl esters and identified using gas chromatography, followed by quantitative evaluation. It has been shown that gas chromatography can be used to assess the composition and authenticity of vegetable oils. Vegetable oils include watermelon, melon and squash oils from melons. Such an approach can be applied in the standardization of the quality of oils, in the development of regulatory documents related to oils
Keywords: Oils; gas chromatography